Evaluation of New Polish Articulation Lists (NAL-93) in the Presence of Various Speech-Like Maskers - SCHELENZ, Anna; SKRODZKA, Ewa (Archives of Acoustics, 2020)
The main goal of the research was to obtain a set of data for ability of speech in noise recognition using Polish word test (New Articulation Lists – NAL-93) with two different masking signals. The attempt was also made to standardise the background noise for Polish speech tests by creating babble noise for NAL-93. Two types of background noise were used for Polish word test – the babble noise and the speech noise. The short method was chosen in the study as it provided similar results to constant stimuli method using less word material. The experiment using both maskers was presented to 10 listeners with normal hearing.The mean SRT values for NAL-93 were −3.4 dB SNR for speech noise and 3.0 dB SNR for babble noise. In this regard, babble noise provided more efficient results. However, the SRT parameter for speech noise was more similar to values obtained for other Polish speech tests. The measurementof speech recognition using Polish word test is possible for both types of masking signals presented in the study. The decision as to which type of noise would be better in practice of hearing aid prosthetics remains an open-end question.